The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0959683617708443
|View full text |Cite
|
Sign up to set email alerts
|

Early- and middle-Holocene wood exploitation in the Fayum basin, Egypt

Abstract: The early and middle Holocene of North Africa was a time of dramatic climatic and social change, including rapid shifts in vegetation communities and the introduction of domesticated plants and animals. Recent research from the Fayum basin of Egypt, which holds archaeological evidence for early use of domesticates, aims to place inhabitants of that region within their contemporary environmental setting. We present here results of wood charcoal analysis from three early-and middle-Holocene deposits on the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 84 publications
(165 reference statements)
1
0
0
Order By: Relevance
“…In prehistoric Fayum, limited, selective coppicing of tamarisk ( Tamarix sp.) yielded only minimal disturbances to overall species abundance of different woodland communities (Marston et al, 2017), similar to the effects reported in the Chad Basin discussed above (Höhn et al, 2021).…”
Section: Late Holocene Human Ecologies Of Africasupporting
confidence: 78%
“…In prehistoric Fayum, limited, selective coppicing of tamarisk ( Tamarix sp.) yielded only minimal disturbances to overall species abundance of different woodland communities (Marston et al, 2017), similar to the effects reported in the Chad Basin discussed above (Höhn et al, 2021).…”
Section: Late Holocene Human Ecologies Of Africasupporting
confidence: 78%